Indirect pulp treatment in a permanent molar: case reort of 4-year follow-up (Journal of Applied Oral Science, 2009)
This case report describes the Indirect Pulp Treatment (IPT) of deep caries lesion in a permanent molar. A 16-year-old male patient reported discomfort associated with thermal stimulation on the permanent mandibular left first molar. The radiographs revealed a deep distal caries lesion, very close to the pulp, absence of radiolucencies in the periapical region, and absence of periodontal space thickening. Pulp sensitivity was confirmed by thermal pulp vitality tests. Based on the main complaint and the clinical and radiographic examinations, the treatment plan was established to preserve pulp vitality. Clinical procedures consisted of removing the infected dentin and lining the caries-affected dentin with calcium hydroxide paste. The tooth was provisionally sealed for approximately 60 days. After this period, tooth vitality was confirmed, the remaining carious dentin was removed, and the tooth was restored. At 4-year follow-up, no clinical or radiographic pathological findings were found.